Air Plasma Activation of Catalytic Sites in a Metal‐Cyanide Framework for Efficient Oxygen Evolution Reaction. Issue 18 (21st February 2018) - Guo, Yanru; Wang, Teng; Chen, Jun; Zheng, Jie; Li, Xingguo; Ostrikov, Kostya (Ken)
Abstract: Targeted activation of highly ordered and distributed metal sites in nanoporous frameworks is a generic strategy to develop high‐performance catalysts. The key challenge is to achieve such activation without damaging the frameworks. Here it is demonstrated that atmospheric‐pressure low‐temperature plasma generated in air improve catalytic properties of an Fe/Co bimetallic cyanide framework through the specific "soft" incorporation of reactive oxygen species without affecting the framework structure. The bonding and oxidative states of the high‐density catalytic metal sites in the framework are modified while the nanoporous nature of the framework is retained, which leads to superior catalytic performance for the oxygen evolution reaction at high current densities close to the operation conditions of commercial alkaline electrolyzers. Abstract : Nondestructive activation of the metal sites in an Fe/Co bimetallic cyanide framework for catalysis by "soft" air plasma: achieving high oxygen evolution activity by creating high density of catalytic active sites without damaging the framework.